ANALYSIS OF DEFAULT RATES IN THE FINTECH LENDING INDUSTRY IN INDONESIA USING TWP90 AND TKB90 INDICATORS - Dewi Fitriana Puji Lestari Dewi; Novita Sari; Muhammad Fauzan (MANKEU (JURNAL MANAJEMEN KEUANGAN), 2025)
The growth of the fintech lending industry in Indonesia continues to increase in line with the high public need for fast and easily accessible digital financing services. However, these developments are also accompanied by an increase in the risk of default that needs to be monitored periodically through the Financial Services Authority's official indicators, namely the 90-Day Default Rate (TWP90) and the 90-Day Payment Success Rate (TKB90). This study aims to analyze the development of these two indicators as a reflection of the level of credit risk in the fintech lending industry during the period from January 2024 to January 2025. The research uses a quantitative descriptive method by utilizing secondary data from OJK monthly publications. The results showed that throughout the observation period, TWP90 was in the range of 2.37%–2.96%, while TKB90 showed stable performance in the range of 97.05%–97.63%. The downward trend in TWP90 in mid-2024 indicates improved credit quality and the effectiveness of risk mitigation, while the increase in TWP90 at the end of the year indicates seasonal pressures affecting borrowers' ability to pay. In addition, the inversely proportional relationship between TWP90 and TKB90 was seen consistent throughout the study period. These findings confirm that although the fintech lending industry is in a relatively healthy and controlled condition, credit risk dynamics still need to be anticipated through the strengthening of risk assessment systems, collection strategies, and periodic monitoring by regulators and industry players.